Accessibility of formal credit among female farmers from Bank of Agriculture (BOA) in Abia State Nigeria - Nnamani, N. G.; Iwezor-Magnus, D. N. (ADAN JOURNAL OF AGRICULTURE, 2024)
The study focused on access to formal credit among female farmers from Bank of Agriculture (BOA) in Abia State Nigeria. The socio-economic characteristics, determinants of credit access among female farmers were examined and determined. A total number of one hundred and fourteen (114) respondents were randomly selected through a multi - stage stratified sampling technique. Primary data were analyzed using descriptive statistical tools such as frequencies, means, percentages and inferential statistic; Logit Regression Model. The mean age (44 years), household size (6 persons), educational level (3.28), farm size (2.51 hectares) and service charge (N19, 789. 47) respectively represents the socioeconomic profile of the female farmers. Logit result identified significant variables that affect the credit access to the farmers to include; farm income (0.113), equity (0.137), marital status (0.114), guarantor (0.052), experience (0.0004), service charge (-0.181) and age (-2.697). It was recommended that improving access to formal credit to female farmers should be encouraged to diversify farm enterprises with the credit obtained from the financial institution by downward review of equity contribution and service charge on credit supplied to the female farmers. It was also recommended that credit be extended to the relatively young people who would be able to embrace new agricultural innovations as to increase their productivity